Quality by Design enabled Development and Optimization of Gastroretentive Floating Matrix Tablets of Dipyridamole - Shah, Harshil P. (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: This research focuses on development and optimization of dipyridamole (DPM) gastroretentive (GR) floating matrix tablets through risk-based approach using combination of rate controlling hydrophilic polymers. Materials and Methods: A 32 full factorial design was deployed to optimize ratio of polymers and polymer concentration in the formulation. Dissolution studies, Buoyancy studies, swelling index studies, kinetic modelling, drug content, and differential scanning calorimetry studies were performed to effectively assess developed gastroretentive dosage form. Estimation of related substances was also done for optimized formulations to check the stability of dosage form during shelf life. Results and Discussion: Buoyancy studies suggested that concentration of PanExceaâ„¢ GR polymer should be at least 25% w/w or more to get better floating and swelling capabilities if used alone as rate controlling polymer. Selection of optimum batches was done using constraint-based graphical optimization technique. The optimum batches exhibited desired extended drug dissolution profile, minimal floating lag time, and total floating time of >12 h. Thermal characterization studies also preclude any drug polymer interaction and change in polymorphic form of drug during manufacturing process. Stability studies indicated optimized formulations are stable under selected packaging configurations. Conclusion: The present research exemplifies successful application of quality by design approach in designing gastroretentive dosage form of DPM. From the present study, it can be concluded that selection of appropriate ratio and concentration of hydrophilic polymers play a pivotal role in matrix integrity, buoyancy, swelling potential as well as drug release profile of GRDDS.